If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4)=2H+1
We move all terms to the left:
(4)-(2H+1)=0
We get rid of parentheses
-2H-1+4=0
We add all the numbers together, and all the variables
-2H+3=0
We move all terms containing H to the left, all other terms to the right
-2H=-3
H=-3/-2
H=1+1/2
| 10y+9=29 | | 10y+9=298 | | 84/11x=14 | | 84/4x=14 | | 84/4x=15 | | 54/2h=3 | | 93/x=3 | | -3a+81=11 | | (2m-7)-(4m-8)=4(m+6) | | -2=t/3 | | -15=5r | | 12x+5+11x=180 | | 103-10x=7 | | n(n-1)=462 | | 5(2x+1)=3(x=4)-5 | | 462=n(n-1) | | 5(11x-18)=3(2x=7) | | -3x+5=12+4x | | 10x=15/20 | | 36+t=75 | | 3.2+x=10 | | 12u=240 | | 238-x=284 | | b/10=27 | | 4x+1=1/2(150-60) | | x-72=20 | | 2(34x+2)=140 | | 56x=693- | | 7y+10=3y+12 | | 2d-1+17+14=55 | | 7x-8=-10+1 | | e/3-8=-2 |